Release of The Rights on Management of PT. Indonesian Port III, (Persero) To The Certificate of Land And Building Connected to Marine Tourism Village in Semarang - M. Ali Mashar; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Land is a natural resource that is essential for human survival. But this time the land is a natural resource that is finite and diminishing. Land has many proprietary someone (private) and state-owned land has been extremely limited. Based on the background mentioned above have been presented, the authors are interested to examine, discuss and review the above issues in the form of a study entitled: